A precarização do trabalho do Assistente Social: estudo nos espaços sócio-ocupacionais público e privado em Parintins/AM - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The theme of this study deals with the precariousness of work, which is due to the process of productive restructuring and counter-reform of the State in the context of the neoliberal offensive in the 1990s in Brazil. The particularity of the study took as its locus the municipality of Parintins in the state of Amazonas. The general objective of the research was to analyze the precarious work of the Social Worker in the public and private socio-occupational spaces in this municipality. In order to achieve this objective, the following specific objectives were defined: to characterize the socio-occupational spaces of the social worker in Parintins-Am; to identify the institutional demands placed on the work of the Social Worker in the public and private socio-occupational space; and to know the perceptions of social workers on the experience of precarious conditions and working relationships in this local Amazonian context. Regarding the methodological procedures, a quantitative and qualitative approach was carried out with the application of questionnaires with closed questions among the universe of 57 social workers and semi-structured interviews with open questions with the sample of 12 professionals working in public and private socio-occupational spaces in Parintins-Am. The operationalization of the study was developed in three complementary phases of data and / or information surveys: bibliographic research, documentary research and field research. The results of the field research revealed the precariousness of the work of social workers both in public and occupational social and occupational spaces. It became evident that the divergences in the precariousness of the work of social workers in these spaces are minimal and can be seen in the contractual and salary flexibility of the professionals. The convergences showed up in excessive work, widespread demand, scarcity of human and material resources that directly affect the conditions in which professionals carry out their work. Another important point pointed out in the results was the reduced number of professionals, which implies work overload, causing illness to workers. In addition, the data revealed that there is a silence on the part of many professionals about the real condition and working relationship in the spaces in which they work. Given this, it is believed that the results of this study brought significant contributions to the municipality of Parintins, in general, as it is a debate that concerns the entire working class. To social workers for giving visibility to their working conditions and relationships in the contemporary Amazonian scenario, giving them the opportunity to broaden the debate and promote reflections on the work of these professionals in the various socio-occupational spaces as well as for carrying out new research in the area of social work for advance in the making and being of the profession in Parintins.
Keywords: Neoliberalismo; Serviço Social; Parintins (Amazonas); Trabalho - Avaliação; Oferta de emprego; CIÊNCIAS SOCIAIS APLICADAS; Neoliberalismo; Serviço Social; Trabalho; Precarização; Parintins